Mecanismos de controle da murcha-de-esclerócio e promoção de crescimento em tomateiro mediados por rizobatérias - Pelzer, Gabriela Queiroz (2010)
This research was aiming to elucidate the antagonism mechanisms responsible for the biocontrol of southern blight and the elements involved in growth promotion in tomato by rhizobacteria. The experimental assays were performed in vivo and in vitro, and the following characteristics evaluated: production of lytic enzymes, antibiosis by volatiles and diffusible compounds, root colonization, siderophores production, carbon sources metabolism, indole acetic acid production, nitrogen fixation, calcium phosphate solubilization and tomato growth promotion in greenhouse conditions. The results indicate that iron competition and antibiosis are mechanisms that explain the biocontrol capability of southern blight by rhizobacteria just as auxin production and biological nitrogen fixation in growth promotion. Limitations in biological control are demonstrated because the competition capability is strain-specific for Sclerotium rolfsii as well antibiosis for nutritional composition of growth media.